Burden in primary informal caregivers of children and adolescents with type 1 diabetes: Is it associated with depression, family dysfunction, and glycemic control? - Balcázar-Hernández, Lourdes; Huerta-Martínez, Hebert; Garrido Magaña, Eulalia; Nishimura-Meguro, Elisa; Jiménez Márquez, Abigail; Rivera-Hernández, Aleida (Frontiers in Endocrinology, 2023)
Objective The requirement of a chronic treatment and the increase in life expectancy in children with type 1 diabetes (T1D) leads to the possibility of caregiver burden. The aim of our study was to evaluate the burden in primary informal caregivers (PIC) of children and adolescents with type 1 diabetes and its association with depression, family dysfunction, and glycemic control. Materials and methods A retrospective study was performed in PIC of children and adolescents with T1D. Zarit Burden Interview Scale (ZBIS) was used to evaluate caregiver burden. Beck Depression Inventory (BDI-II) was used to evaluate depression in PIC, and the Family APGAR questionnaire was used to evaluate the family functionality. Results A total of 100 PIC of children and adolescents with T1D were included. Caregiver burden was found in 33% of caregivers. The total score of the Zarit scale was 41 (34–49); 19% had mild caregiver burden, and 14% had severe caregiver burden. According to the BDI-II, 82% had minimal depression, 11% mild depression, 5% moderate depression, and 2% severe depression. Family function was good in 69%; 13% had moderate dysfunction, and 18% had severe dysfunction. A positive correlation between caregiver burden and BDI-II score (r = 0.84; p = 0.001) and the grade of depression (r = 0.87; p = 0.001) was found. A logistic regression model showed that BDI-II score was associated with caregiver burden (OR 1.14; 95% CI 1.061–1.23; p = 0.001). A BDI-II cut off of 9 or more had a sensibility and specificity of 58% and 28%, respectively, for caregiver burden [AUC 0.751 (0.64–0.85); p = 0.001]. A BDI-II score ≥9 was a predictor of caregiver burden (OR 3.4; 95% CI 1.4–8.1; p = 0.008). Conclusion Caregiver burden is present in more than one third of the PIC of patients with T1D and is associated with depression. A BDI-II score ≥9 is a predictor of caregiver burden which may be a point to take into account in the integral approach to the patient with T1D and his or her family nucleus.